Arterioportal Fistulas in Liver Transplant Recipients - Saad, Wael E. A. (Seminars in Interventional Radiology, 2012)
Arterioportal fistulas (APFs) are classified into intrahepatic (>75% of all reported) and extrahepatic (<25% of all reported ). Anecdotally, investigators are more likely to report more sensational cases (typically extrahepatic APFs), so the actual prevalence of intrahepatic APFs is probably much higher (likely >90% of APFs). All reported APFs in liver transplant recipients have been intrahepatic. Hemodynamically significant APFs in liver transplant recipients are rare, occurring in 0.2%; however, APFs (hemodynamically significant or not) are not uncommonly seen in hepatic angiograms of liver transplant recipients (up to 5.4% of hepatic arteriograms in transplants). Interestingly, hemodynamically significant APFs warranting endovascular treatment are reported more commonly in the literature in native compared with transplanted livers (n >280–300 versus n = 13, respectively). This article discusses APFs that are specific to liver transplant recipients; their incidence, etiology, pathogenesis, natural history, clinical presentation, and endovascular management are discussed in detail.
Keywords: transplant; liver; vascular complications; endovascular; portal; arterial; fistula; embolization